Sphingolipid long-chain-base auxotrophs of Saccharomyces cerevisiae: genetics, physiology, and a method for their selection. - Pinto, W J (1992)
A selection method for sphingolipid long-chain-base auxotrophs of Saccharomyces cerevisiae was devised after observing that strains that require a long-chain base for growth become denser when starved for this substance. Genetic analysis of over 60 such strains indicated only two complementation classes, lcb1 and lcb2. Mutant strains from each class grew equally well with 3-ketodihydrosphingosine, erythrodihydrosphingosine or threodihydrosphingosine, or phytosphingosine. Since these metabolites represent the first, second, and last components, respectively, of the long-chain-base biosynthetic pathway, it is likely that the LCB1 and LCB2 genes are involved in the first step of long-chain-base synthesis. The results of long-chain-base starvation in the Lcb- strains suggest that one or more sphingolipids have a vital role in S. cerevisiae. Immediate sequelae of long-chain-base starvation were loss of viability, exacerbated in the presence of alpha-cyclodextrin, and loss of phosphoinositol sphingolipid synthesis but not phosphatidylinositol synthesis. Loss of viability with long-chain-base starvation could be prevented by also blocking either protein or nucleic acid synthesis. Without a long-chain-base, cell division, dry mass accumulation, and protein synthesis continued at a diminished rate and were further inhibited by the detergent Tergitol. The cell density increase induced by long-chain-base starvation is thus explained as a differential loss of cell division and mass accumulation. Long-chain-base starvation in Lcb- S. cerevisiae and inositol starvation of Inos- S. cerevisiae share common features: an increase in cell density and a loss of cell viability overcome by blocking macromolecular synthesis.